Feeding minds, fueling futures: How School Feeding Programs (SFP) drive development in low-Income nations like Ethiopia - Zerfu, Taddese Alemu (ANH Academy, 2024)
Ethiopian households face daunting challenges due to inflation, conflict, drought, climate change, and the COVID-19 pandemic.